HBT and initial conditions for hydrodynamic expansion in A+A collisions - Gyulassy,M. (2007)
The behavior of interferometry radii in central A+A collisions at different energies and also for different nuclei or impact parameters indicates initial transverse flow at a very early stage of the matter evolution. Development of such flow at the pre-thermal partonic stage is considered.